PROFESSIONAL IDENTITY CONSTRUCTION: EFL PRE-SERVICE TEACHERS’ CHALLENGES IN DOING TEACHING PRACTICUM AT PUBLIC PRIMARY SCHOOLS - Emyliana Emyliana; Yunika Upa (Teaching English and Language Learning English Journal, 2025)
This study explores the challenges experienced by pre-service English as a foreign language (EFL) teachers during their teaching practicum at SDN Seluang Danau and SDN Semata. This study aims to explore the challenges faced by EFL pre-service teachers during their teaching practicum at SDN Seluang Danau and SDN Semata, and to investigate the influence of these challenges on the EFL pre-service teachers’ professional identity construction. The method used was a qualitative approach with lived experience, data were collected through semi-structured interviews with 4 EFL pre-service teachers who had conducted teaching practicum in the two schools. The results showed that the participants faced various challenges, including difficulties in applying appropriate teaching methods, difficult classroom management, and limited facilities. These challenges had a significant impact on their professional identity formation process, with most participants feeling insecure and pressured by expectations of being an ideal teacher. Nonetheless, the experience during teaching practicum provided opportunities for them to learn, adjust to the environment, and develop strategies to overcome problems that arose. Adequate support from educational institutions and mentors is crucial for pre-service teachers to face challenges and build a strong professional identity. This study opens up opportunities for further research related to efforts to develop pre-service teachers' professional identity in various diverse contexts, and emphasizes the importance of adapting the curriculum to meet specific needs in remote areas.